ANALISIS PENGARUH KEPUASAN KERJA, IKLIM ORGANISASI KOMITMEN ORGANISASI TERHADAP EFEKTIVITAS ORGANISASI : ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI MEDIASI - Muhammad Harri (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This study aims to determine the influence of job satisfaction, organizational climate, organizational commitment and organizationa citizenship behavior on organizational effectiveness in PT. Cosmo Makmur Indonesia. Population and sample ini this study in the number of employee of 169 people. Analysis the data used was the validity and reliability test with path analysis. From the analysis, the coefficient of the determinan (R2) noted that organizational citizenship behavior influenced by job satisfaction, organizational climate, organizational commitment by 87% and the ramining 13% was influence by other factors which not included in the model. Job satisfaction significantly effect of 3.540, organizational climate siginificantly effect of 2,889 and organizational commitment significantly effect of 2,108 and organizational citizenship behavior significantly effect of 6.862. The analysis of the test, yhe coefficient of the determination noted that the organizational effectiveness was influenced by job satisfaction, organizational climate, organizational commitment, and organizational citizenship behavior.